Military Emerging Disruptive Technologies: Compliance with International Law and Ethical Standards - Marsili, M. (Intelligent and Autonomous: Emergent Digital Technologies and the Challenges of Disinformation, Security, and Regulation, 2021)
Military emerging disruptive technologies (EDTs) have a rapid and major effect on technologies that already exist and disrupt or overturn traditional practices and may revolutionize governmental structures, economies and international security. Margaret Kosal (2019) finds that military applications of EDT have even greater potential than nuclear weapons to radically change the balance of power. The debate, stimulated by the Group of Governmental Experts on emerging technologies in the area of lethal autonomous weapons systems (GGE on LAWS) established by the Convention on Prohibitions or Restrictions on the Use of Certain Conventional Weapons (CCW), has focused on artificial intelligence, cyber weapons and drones. A broader discussion should include all military EDTs, inter alia: space and hypersonic weapons; directed-energy weapons/laser and photonic weapons, just to name a few. Though leaders have begun to become aware of legal and ethical implications of the military use of EDTs, these issues remain in the background: security concerns are of pivotal importance and a most of the information and documents are kept confidential and their circulation is restricted. This paper aims to investigate the compliance of military EDTs with international law, international humanitarian law, international human rights law and with ethical principles.